Kerkregtelike perspektiewe op die “intensie van die partye” met die beroeping en bevestiging van predikante - Smit, J (Nederduitse Gereformeerde Teologiese Tydskrif, 2009)
Church polity perspectives on the “intention of the parties” with the calling and ordination of ministers According to South African courts the main question to be asked for an evaluation of the relationship between a minister of religion and a congregation is: what was the “intention of the parties” with the calling and ordination of a minister? The answer to this question serves as an indication either for the application of labour law on the regulation of a minister’s service or that the church has the authority to regulate the service via the applicable order or constitution of the Church. In this article the “intention of the parties” with the calling and ordination of a Reformed minister is evaluated in the light of Scriptures, the Confession of the Church, the Church Order of the Reformed Churches in South Africa, the concept form of the letter of calling and the Formulary for the Ordination of a Minister. In conclusion it is found that the “intention of the parties” is not to regulate the service of a minister on the basis of a contractual relationship, but service to God according the principles He gave in Scriptures as it is formulated in the Confessions and regulated by the Church Order.